Zimbabwe : 2009 Article IV Consultation-Staff Report; Public Information Notice on the Executive Board Discussion; and Statement by the Executive Director for Zimbabwe. (IMF Staff Country Reports; Country Report ;, 2009)
Economic and social indicators in Zimbabwe worsened significantly in 2008. Real GDP is estimated to have fallen by about 14 percent in 2008 owing to economic disruptions caused by hyperinflation and a further significant deterioration in the business climate. Executive Directors have welcomed the authorities' Short-Term Emergency Recovery Program (STERP) that is based on sound principles of macroeconomic management. Directors have also underscored the importance of establishing fiscal discipline while ensuring the delivery of essential public services.